Evidence-based Strategies in Herbal Medicine, Psychiatric Disorders and Emergency Medicine - Badria, Farid A. (IntechOpen, 2015)
This book intends to strike a balance between developments in pharmacotherapy research and the facts that researchers must absorb, as well as link scientific advances with clinical practice so that the management of diseases can be based on sound physiological concepts. Each chapter has been reviewed and new authors have brought up-to-date research to make the book more informative, illustrative, and easy to read. The book focuses on three major areas: Experimental, preclinical, and clinical applications of herbal medicine; Evidence-based strategies in emergency medicine and New approach in management of psychiatric disorders. The first three chapters describe new and modern applications of common herbs for treatment of several inflammatory and skin disorders, e.g. ulcerative colitis, bronchial asthma, osteoarthritis, multiple sclerosis, and melasma. Chapter four deals with the most severe hypertensive states that pose an immediate threat to life, and how to manage these situations. The fifth chapter is dedicated to tackling polypharmacy psychiatric disorders. We hope this book is useful to a wide range of readers, from students first learning about pharmacotherapy, through advanced clinicians and researchers who are looking for a review of current treatments and conceptualizations of the condition. It is our hope that this book may motivate readers to approach the evidence on pharmacotherapy with an open mind, and thereby spark an interest in initiating further contributions to the current scientific debate and treatment development efforts.